PENGARUH KULTUR ORGANISASI DAN GAYA DALAM KEPEMIMPINAN TERHADAP PERFORMA GENERASI Z PADA PERUSAHAAN/STARTUP YANG ADA DI SBM ITB - Wafiuddin Azzulfa W., Falah
Culture is regularly reenacted and generated by our experiences with others. Formed value of others, we think of that as "leadership" and are creating the conditions for new culture creation. Culture and leadership are two sides of the same coin in that leaders first initiate the sequence of culture formation when they create entities and organizations. Leadership may also be regarded as a critical factor in bringing about a profitable business for the company. However, a leadership style is usually used by a manager to fulfil their responsibilities and duties within the business and organization. In general, the problem caused by the authoritative people such as somebody with the position, particularly our leader, is often frustrating or difficult to us. Although people with more experience in the company cannot guarantee that all workers are satisfied with their style in a leading the organization, and many successful organizations with a good standard of leadership make employees more productive. Just as our start-up Kooka did (start-up, augmented reality technology enabler) who chose the leader based on their background in the previous company, he acts and leads in the same way, before he actually thinks that start-up management is different from the organization. The main purpose of this research is to determine the relation of leadership style, and the relationship between organizational culture and Z generation performance, and what type of leadership style may contribute to the performance of Z generation. After all, this has been established, and the aim is to find the best combination since these features in order to improve employee performance in general and especially in Z generation. As a possible consequence, overall performance can be continued to improve in the organization. The researcher gathers data from questionnaires and analyses data to identify a variety of descriptive and statistical results. For the Transformational and Transactional Leadership questionnaire itself was also split into five personal questions based on behavioral findings on 10 percent of the overall sample and then, to analyze the relation of independent and dependent the researcher will use Multiple Linear Regression with the classical assumption test first. The result showed form the 70 sample of SBM ITB student that hierarchy culture will improve the employee performance especially on their behavioral engagement and for the leadership variable the transformational leadership has a significance relationship to employee performance but the result has showed that leadership style have the negative impact while performed. This also showed that transactional skills are important for all members. Yet in a world in which success relies on quality change, businesses also need transformational leaders in the simplest case as an approach to leadership that causes changes in individuals and social institutions and leads followers to change desirably and productively. Today, organizations need workers to adapt to technical developments with emerging global challenges. Compared with transaction leaders, transformational leadership appear to test their followers in order to determine their motives. Nonetheless, the adverse association between leadership styles and performance was quite important, more research should be carried out to strengthen these ties.